2018
DOI: 10.1080/02699931.2018.1450225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cognitive bias modification-memory on depressive symptoms and autobiographical memory bias: two independent studies in high-ruminating and dysphoric samples

Abstract: (2018): Effect of cognitive bias modification-memory on depressive symptoms and autobiographical memory bias: two independent studies in high-ruminating and dysphoric samples, Cognition and Emotion,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 54 publications
5
25
1
1
Order By: Relevance
“…This is corroborated by in the awareness check data, where some subjects reported that they felt better as a result of their difficulty recalling negative events. This is also in line with earlier findings by Vrijsen et al (2018), where only dysphoric individuals with an initial positive processing style showed more positive autobiographical memory bias after positive MBM, suggesting that it may be more difficult to revert a pre-existing negative memory bias as seen in depression.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is corroborated by in the awareness check data, where some subjects reported that they felt better as a result of their difficulty recalling negative events. This is also in line with earlier findings by Vrijsen et al (2018), where only dysphoric individuals with an initial positive processing style showed more positive autobiographical memory bias after positive MBM, suggesting that it may be more difficult to revert a pre-existing negative memory bias as seen in depression.…”
Section: Discussionsupporting
confidence: 92%
“…Several distinct subtypes of CBM have been developed, each targeting different cognitive domains such as attention (Attention bias modification/ABM; MacLeod et al 2002), interpretation (Interpretation Bias Modification/CBM-I; Yiend et al 2005), approach-avoidance (Approach-avoidance training/AAT; Rinck and Becker 2007) and memory (Memory bias modification/MBM; Vrijsen et al 2016;Hertel et al 2017;Vrijsen et al 2018). Initial lab-based MBM studies in unselected samples have shown promising results (Vrijsen et al 2016;Hertel et al 2017;Arditte Hall et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bisher deuten die aktuellen Studien darauf hin, dass 4 Sitzungen des CBM-Positivitätstrainings depressive Symptome klinisch relevant verringern können (Becker et al 2019). Auch sollten weitere Studien die verschiedenen Modalitäten untersuchen: So kann beispielsweise ein CBM-Interpretationstraining effektiver sein als ein CBM-Aufmerksamkeitstraining (Cristea et al 2015), wobei eine gedächtnisspezifische CBM einen neuen Ansatz darstellt (Vrijsen et al 2019). Bei einem solchen Training werden Patienten trainiert, positive Stimuli durch wiederholte Retrieval-Prozesse besser zu erinnern.…”
Section: Vor-und Nachteile Der Studieunclassified